A Survivor Following Repair of Laryngotracheo-Esophageal Cleft: Lessons Learned - Ratan, Simmi K.; Ratan, John; Vinay, Becshea; Seth, Rajiv (American Journal of Perinatology, 2002)
A survivor, following successful repair of laryngotracheo-esophageal cleft extending up to cervical trachea, is being described. The cleft was repaired with anterior laryngofissure approach, using no interposition of tissue between trachea and esophagus. The patient had an uneventful recovery, short hospitalization, and satisfactory outcome on follow-up for over 11/2 years, as of now. Optimum ventilation was achieved intra-operatively via an endotracheal tube passed through operative field, following visualization of the cleft. Postoperatively, mechanical ventilation was given via nasotracheal tube left indwelling in trachea following completion of tracheal repair. Early nutrition through enteral route was started 72 hours postoperatively by drip feeds (using infusion pump) through a soft nasogastric tube that was left indwelling following esophageal repair. This maneuver, along with positional and medical therapy, helped us to gain control over gastro-esophageal reflux that is known to be incapacitating in these patients. The authors recommend a reexamination of existing management strategies for patients with laryngotracheo-esophageal clefts and suggest that conservative approach in dealing with associated problems can help decrease morbidity in these patients.
Keywords: Laryngotracheo-esophageal cleft; survivor; ventilation; gastro-esophageal reflux